A Novel IL3-ETV6 Fusion in Chronic Eosinophilic Leukemia Not Otherwise Specified With t(5; 12) (q31; p13): A Case Report and Literature Review - Zhao, Cenzhu; Wang, Man; Zhan, Yuchen; Xu, Yang; Chen, Suning; Wang, Qinrong; An, Jingnan; Liu, Tianhui (Frontiers in Oncology, 2022)
Chronic eosinophilic leukemia not otherwise specified (CEL-NOS) is classified as Myeloproliterative Neoplasms (MPN) and refers to chronic eosinophilic leukemia with some atypical recurrent genetic evidence(1). A rare fusion of ACSL6-ETV6 was previously identified in patients with the t(5;12) (q31; p13) karyotype(2). Here, we report a case of CEL-NOS with a translocation of t(5;12) (q31; p13) and identify IL3-ETV6 transcription, which has not been identified in hematologic diseases. In this patient, eosinophilia was observed. And compared with CEL-NOS patients without ETV6 fusion, a higher mRNA expression level of IL3 was found. After failing treatment with dasatinib, the patient was given hydroxyurea (HU). Subsequently his white blood cell (WBC) and eosinophils decreased significantly and remained in the normal range until publication. Due to the side effects, treatment with HU was replaced by PEG-interferon (PEG-IFN). What’s more, we summarized the case in our study and 21 patients with the karyotype of t(5; 12) (q31; p13) reported by other groups. It was found that most of them had similar clinical manifestations of eosinophilia and tyrosine kinase inhibitor (TKI) insensitivity. The ectopic mRNA expression of IL3 may be the main cause of eosinophilia, and HU and prednisone acetate (PAT), as well as IFN, were considered treatments for this group.